The effect of prosocial behaviour manageability on conscious awareness in university athletes: The mediating role of athlete identity - Unal Saki; Mehmet Oztas (ROL Spor Bilimleri Dergisi)
It has been suggested that there is a reciprocal and in-depth relationship between prosocial behaviors, mindfulness, and athlete identity. While athlete identity may contribute to the development of mindfulness by encouraging prosocial behaviors, mindfulness may also play an important role in understanding the internal structure of athlete identity and exhibiting prosocial behaviors. The interaction between these three components is thought to significantly affect athletes’ social and psychological development. In this context, this study aimed to investigate the effect of university athletes’ prosocial behavior manageability on mindfulness and the mediating role of athlete identity on this relationship. This study included 189 sports science faculty students who competed at least three times in university leagues. The Personal Information Form’, ‘Mindfulness Scale, and Prosocial Behavior Scale prepared by the researcher were used in the data collection part of the study. Multiple linear regression analysis was used to analyze the data. Statistical calculations were performed using the Jamovi package program. The results of this study show that athlete identity plays an important mediating role in the effect of prosocial behaviors on mindfulness. This situation sheds light on the development of strategies that can contribute to both individual development of athletes and team dynamics. Although the direct effect was not statistically significant, the manageability of prosocial behaviors may have a significant effect on mindfulness through the mediating role of athlete identity. These findings suggest that strengthening athlete identity may be an effective strategy for transforming athletes’ prosocial behaviors into mindfulness.